2020
DOI: 10.1021/acsanm.0c01010
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Self-Assembly of Silver Nanoparticles for Rapid Generation of First and Second Surface Mirrors

Abstract: Interesting mirror-like, highly reflective, and conductive silver films have been successfully generated directly on a glass slide using a simple and fast photoinduced approach. A water-based photosensitive formulation containing the silver precursor and a photogenerator of free radicals was used. It was applied like paint and exposed to UV light for a few seconds, in the absence of any additional reducing agents and without further treatment of any kind. This approach allowed ultrathin films of silver nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The formation of a silver layer on a glass surface has been well-known for several decades and described in multiple studies [ 39 , 40 , 41 , 42 , 43 , 44 ] and patents [ 45 , 46 , 47 ] by applying various techniques. The most-common silver-deposition reaction is based on Tollens’ reagent, which is a colorless solution of a diamminesilver(I) complex that is created by a mixture of silver nitrate, ammonia, and alkaline [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The formation of a silver layer on a glass surface has been well-known for several decades and described in multiple studies [ 39 , 40 , 41 , 42 , 43 , 44 ] and patents [ 45 , 46 , 47 ] by applying various techniques. The most-common silver-deposition reaction is based on Tollens’ reagent, which is a colorless solution of a diamminesilver(I) complex that is created by a mixture of silver nitrate, ammonia, and alkaline [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6, the characteristic absorption peak of the dye at 390 nm gradually decreased upon visible light irradiation, indicating that the dye interacted with Iod/EDB. At the same time, a new absorption peak appeared at 430 nm and its absorbance gradually increased, which indicated that the Ag + cations were reduced into AgNPs [45,46]. In addition, the solution changed from light yellow to yellow-brown during the light irradiation process, and a yellowbrown silver nanoparticle coating was observed on the side of the cuvette.…”
Section: Agnps Generated In Dmf Solution and Ipn-polymersmentioning
confidence: 97%
“…For instance, for the controlled assembly of silver nanoparticles on a polyimide substrate, the method of convective self-assembly was used, and as a result, homogeneous coatings with high conductivity were obtained, which can be used as electrodes for sensors [46]. Photoinduced self-assembly of silver nanoparticles on a glass substrate allowed obtaining ultrathin AgNPs films, exhibiting high reflective and conductive properties for the use in optics and electronics [47]. A metamaterial based on silver nanoparticles with a thermosensitive coating demonstrated active self-assembly of AgNPs as a result of temperature-dependent changes in the organic coating.…”
Section: Synthesis and Self-assembly Of Biogenic Silver Nanoparticlesmentioning
confidence: 99%